The 'Continuous Exposition' and the Concept of Subordinate Theme. (11th December 2015) - Caplin, William E.; Martin, Nathan John
ABSTRACT: James Hepokoski and Warren Darcy's Sonata Theory promotes a fundamental distinction between sonata expositions that are either two‐part or continuous . We contend that this binary opposition misconstrues the commonality of formal procedures operative in Classical sonata form. Advocating a form‐functional approach, we hold that all sonata expositions contain a subordinate theme (or at least sufficient functional elements of such a theme), even if the boundary between the transition and subordinate theme is obscured. We illustrate three categories of such a blurred boundary: (1) the transition lacks a functional ending but the subordinate theme still brings an initiating function of some kind; (2) the transition ends normally but the subordinate theme lacks a clear beginning; and (3) the transition lacks an ending and the subordinate theme lacks a beginning, thus effecting a complete fusion of these thematic functions. We extend these considerations to another formal type – minuet form – in order to place the technique of fusion as it arises in sonata‐form expositions in a broader perspective. In further comparing a theory of formal functions to Sonata Theory, we invoke the 'sonata clock' metaphor, first introduced by Hepokoski and Darcy, and show that our respective clocks have different 'hour' markers and run at different speeds. We conclude by examining some of the main conceptual differences that account for the divergent views of expositional structures offered by Sonata Theory and a theory of formal functions, arguing against the former's claim that the medial caesura is a necessary condition for the appearance of a subordinate theme.